Oral administration of non-absorbable delayed release 6-mercaptopurine is locally active in the gut, exerts a systemic immune effect and alleviates Crohn's disease with low rate of side effects: results of double blind Phase II clinical trial. (14th July 2015) - Israeli, E; Goldin, E; Fishman, S; Konikoff, F; Lavy, A; Chowers, Y; Melzer, E; Lahat, A; Mahamid, M; Shirin, H; Nussinson, E; Segol, O; et al.
Summary: Therapy for Crohn's disease (CD) with thiopurines is limited by systemic side effects. A novel formulation of fixed-dose, delayed-release 6-mercaptopurine (DR-6MP) was developed, with local effect on the gut immune system and minimal absorption. The aim of this study was to evaluate the safety and efficacy of DR-6MP in patients with moderately severe CD compared to systemically delivered 6-mercaptopurine (Purinethol). Seventy CD patients were enrolled into a 12-week, double-blind controlled trial. The primary end-point was the percentage of subjects with clinical remission [Crohn's Disease Activity Index (CDAI) < 150] or clinical response (100-point CDAI reduction). Twenty-six (56·5%) and 13 (54·2%) subjects from the DR-6MP and Purinethol cohorts, respectively, completed the study. DR-6MP had similar efficacy to Purinethol following 12 weeks of treatment. However, the time to maximal clinical response was 8 weeks for DR-6MP versus 12 weeks for Purinethol. A higher proportion of patients on DR-6MP showed clinical remission at week 8. A greater improvement in Inflammatory Bowel Disease Questionnaire (IBDQ) score was noted in the DR-6MP group. DR-6MP led to a decrease of CD62 + expression on T cells, implying a reduction of lymphocyte adhesion to site of inflammation. DR-6MP was safer than Purinethol, with significantly fewer adverse events (AEs). There was no evidence of drug-induced leucopenia in the DR-6MP group; the proportion of subjects who developed hepatotoxicity was lower for the DR-6MP. Non-absorbable DR-6MP is safe and biologically active in the gut. It is clinically effective, exerting a systemic immune response with low systemic bioavailability and a low incidence of side effects.